Efficient and Broadband LiGaP2O7:Cr3+ Phosphors for Smart Near‐Infrared Light‐Emitting Diodes. Issue 11 (11th October 2021) - Yuan, Chenxu; Li, Ruiyang; Liu, Yongfu; Zhang, Liangliang; Zhang, Jiahua; Leniec, Grzegorz; Sun, Peng; Liu, Zehua; Luo, Zhaohua; Dong, Rui; Jiang, Jun
Abstract: Broadband near‐infrared (NIR) phosphor‐converted (pc) LED is promising next‐generation tiny light source for smart and broadband NIR spectroscopy technology. However, NIR phosphors suffer from challenges in terms of low quantum efficiency and bandwidth. By selecting a host that has a big bandgap and weakening coupling effect among Cr 3+, a novel LiGaP2 O7 :Cr 3+ (LGAP:Cr 3+ ) NIR phosphor that has a high external quantum efficiency (28.3%) is discovered. Under ≈450 nm excitation, LGAP:Cr 3+ shows broad NIR emission from 700 to 1100 nm with a bandwidth of ≈170 nm. Importantly, the fabricated pcLED demonstrates bright broadband NIR light and an excellent performance in night vision. The results promise the use of the LGAP:Cr 3+ phosphor for high‐performance broadband NIR LED that employs only one tiny blue LED chip. Abstract : Opening the bandgap of the LiGaP2 O7 (LGAP) host and decreasing the coupling effect of Cr 3+ to the host, LGAP:Cr 3+ shows efficient and broadband near‐infrared (NIR) emission from 700 to 1100 nm. The fabricated NIR light‐emitting diode (LED) based on a blue chip and LGAP:Cr 3+ phosphors shows bright NIR light peaked around 846 nm with a bandwidth of 168 nm.